The Academic Workplace Country Report Poland - Kwiek, Marek (My University, 2004)
The changes in recent decade in Poland have been dramatic, for all professions and all workplaces, including those in the academy. Apparently, transformations in the academy have been much less radical and prolonged in time; higher education systems cannot be changed overnight, and the fact became obvious after the new law on higher education was adopted in Poland in 1990, and then, despite numerous attempts, it was not followed by further major legal changes until the present (2003). It is thus important to stress that after the changes following the collapse of communism in Poland in 1989 and the new law on higher education that was adopted in 1990, hardly any new changes regarding employment and working conditions in the academy occurred in strictly legal terms. The law on higher education today is 13 years old, and although a dozen or so attempts to adopt a new law had been taken, by almost all stakeholders, none of the proposals was finally accepted.
Keywords: Poland; Polish higher education; Polish academic profession; Polish academics; Polish universities; workplace; working conditions; academic salaries; transition countries; Central Europe; Central and Eastern Europe; postcommunist countries; reforms; law on higher education; academic freedom; institutional autonomy